2010
DOI: 10.1021/jf9035172
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Syringyl to Guaiacyl Ratio on the Structure of Natural and Synthetic Lignins

Abstract: Several kinds of natural woods and isolated lignins with various syringyl to guaiacyl (S/G) ratios were subjected to thioacidolysis followed by Raney nickel desulfuration to elucidate the relationships between the S/G ratio and the interunit linkage types of lignin. Furthermore, enzymatic dehydrogenation polymers (DHP) were produced by the Zutropf (gradual monolignol addition) method from mixtures of various ratios of coniferyl alcohol and sinapyl alcohol. The analysis of DHPs and natural wood lignins exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(101 citation statements)
references
References 15 publications
(29 reference statements)
5
85
2
3
Order By: Relevance
“…At the current state of investigations, we can only speculate on reasons for the higher reactivity of S-rich lignin. Generally, S-rich lignin features predominantly linear chains with less cross-linking than G-rich lignin because of the methoxylated and thereby, blocked C-5 position in the syringyl unit (20), resulting in fewer highly stable 5-5 and β-5 linkages (20)(21)(22). The higher occurrence of β-β units (resinols) in S-rich lignin leads to shorter chain lengths and thus, lower molecular weights (21), which potentially alter thermoplastic properties, including lowering melting points (13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the current state of investigations, we can only speculate on reasons for the higher reactivity of S-rich lignin. Generally, S-rich lignin features predominantly linear chains with less cross-linking than G-rich lignin because of the methoxylated and thereby, blocked C-5 position in the syringyl unit (20), resulting in fewer highly stable 5-5 and β-5 linkages (20)(21)(22). The higher occurrence of β-β units (resinols) in S-rich lignin leads to shorter chain lengths and thus, lower molecular weights (21), which potentially alter thermoplastic properties, including lowering melting points (13).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, S-rich lignin features predominantly linear chains with less cross-linking than G-rich lignin because of the methoxylated and thereby, blocked C-5 position in the syringyl unit (20), resulting in fewer highly stable 5-5 and β-5 linkages (20)(21)(22). The higher occurrence of β-β units (resinols) in S-rich lignin leads to shorter chain lengths and thus, lower molecular weights (21), which potentially alter thermoplastic properties, including lowering melting points (13). The relative amount of chemically labile β-O-4 ether linkages has been shown to remain constant independent of the S/G ratio if at least some syringyl units are present (20,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the extraction of HRML and PML, the dioxane/ water-extracted residues were washed with water more than once and then treated with a mixture of same volume of Aspergillus niger cellulase (Sigma) and A. niger hemicellulase (Sigma) (32 mg/ml each enzyme) dissolved in 0.2 M sodium acetate buffer (pH 4.8) at 37°C for 72 h. After filtration through a nylon cloth, the insoluble residues were washed with a large amount of water, and the LREL and PEL samples were obtained by successive extractions with 90 and 50% dioxane/water as before. Klason lignin content in each fraction was determined by measuring the yield of insoluble residues after treating with sulfuric acid according to the standard procedure with slight modification as described previously (24). The sulfuric acid-soluble fraction was used for determining the neutral sugar composition (see below).…”
Section: Methodsmentioning
confidence: 99%
“…However, a lower ratio (0.2) indicated that the negative influence of lignin was less apparent and that the sugar release was 60% higher. The increase in digestibility from combined pretreatment and enzymatic hydrolysis with a decreased concentration ratio of lignin-tocarbohydrates was mainly related to the more labile β-O-4 bonds in S-lignin during the pretreatment (Kishimoto et al 2010). Since it has been confirmed that lower ratio of ligninto-carbohydrate could be more helpful to increase the sugar release in fermentation process, 1-year-old E. ulmoides with lower ratio of lignin-to-carbohydrate than 3-year-old E. ulmoides would be preferable raw materials for biofuels.…”
Section: Topochemical Correlation Between Carbohydrates and Lignin Inmentioning
confidence: 99%